A STRATEGIC FRAMEWORK FOR INTEGRATED GOVERNANCE, RISK, AND COMPLIANCE (GRC) AND SUSTAINABILITY AT TELKOM INDONESIA - Liza Mahavianti Syamsuri (Journal of Social and Economics Research, 2025)
Integrating Governance, Risk, and Compliance (GRC) with Environmental, Social, and Governance (ESG) principles is crucial for large enterprises like Telkom to achieve sustainable growth and build stakeholder trust. Telkom has a solid foundation in both areas, with robust corporate governance, ISO 31000:2018-aligned risk management, and comprehensive compliance policies. Its "GoZero%" program demonstrates a strong commitment to ESG, supported by consistent international reporting. However, full integration faces challenges like data fragmentation, ESG data inconsistencies, and a dynamic regulatory landscape. Telkom also deals with potential political interference and capacity limitations as a state-owned enterprise. Despite these hurdles, integration offers significant opportunities: enhanced holistic risk mitigation, improved operational efficiency through unified data, and increased stakeholder trust via transparent reporting. Leveraging AI can further streamline data management and automate compliance. This paper proposes a strategic framework for Telkom, emphasizing strong leadership, improved data governance, embedding ESG into enterprise risk management, robust sustainability compliance, and fostering an ethical culture for a more sustainable and resilient future.